Potential impacts of marine fuel regulations on an Arctic stratocumulus case and its radiative response - L. F. Escusa dos Santos; L. F. Escusa dos Santos; H. C. Frostenberg; A. Baró Pérez; A. M. L. Ekman; A. M. L. Ekman; L. Ickes; E. S. Thomson (Atmospheric Chemistry and Physics)
Increased surface warming over the Arctic triggered by increased greenhouse gas concentrations and feedback processes in the climate system has been causing a steady decline in sea-ice extent and thickness. With the retreating sea ice, shipping activity will likely increase in the future, driven by economic activity and the potential for realizing time and fuel savings from using shorter trade routes. Moreover, over the last decade, the global shipping sector has been subject to regulatory changes that affect the physicochemical properties of exhaust particles. International regulations aiming to reduce SOx and particulate matter (PM) emissions mandate ships to burn fuels with reduced sulfur content or, alternatively, use wet scrubbing as an exhaust aftertreatment when using fuels with sulfur contents exceeding regulatory limits. Compliance measures affect the physicochemical properties of exhaust particles and their cloud condensation nucleus (CCN) activity in different ways, with the potential to have both direct and indirect impacts on atmospheric processes such as the formation and lifetime of clouds. Given the relatively pristine Arctic environment, ship exhaust particle emissions could cause a large perturbation to natural baseline Arctic aerosol concentrations. Low-level stratiform mixed-phase clouds cover large areas of the Arctic region and play an important role in the regional energy budget. Results from laboratory marine engine measurements, which investigated the impact of fuel sulfur content (FSC) reduction and wet scrubbing on exhaust particle properties, motivate the use of large-eddy simulations to further investigate how such particles may influence the micro- and macrophysical properties of a stratiform mixed-phase cloud case observed during the Arctic Summer Cloud Ocean Study campaign. Simulations with diagnostic ice crystal number concentrations revealed that enhancement of ship exhaust particles predominantly affected the liquid-phase properties of the cloud and led to decreased liquid surface precipitation, increased cloud albedo, and increased longwave surface warming. The magnitude of the impact strongly depended on ship exhaust particle concentration, hygroscopicity, and size, where the effect of particle size dominated the impact of hygroscopicity. While low-FSC exhaust particles were mostly observed to affect cloud properties at exhaust particle concentrations of 1000 cm−3, exhaust wet scrubbing already led to significant changes at concentrations of 100 cm−3. Additional simulations with the cloud ice water path increased from ≈ 5.5 to ≈ 9.3 g m−2 show more-muted responses to ship exhaust perturbations but revealed that exhaust perturbations may even lead to a slight radiative cooling effect depending on the microphysical state of the cloud. The regional impact of shipping activity on Arctic cloud properties may, therefore, strongly depend on ship fuel type, whether ships utilize wet scrubbers, and ambient thermodynamic conditions that determine prevailing cloud properties.